The effect of magnesium ions on the vesicular-arbuscular mycorrhizal infection of maize roots - Gryndler, M; Vejsadová, H; Vančura, V (The New phytologist, 1992)
The effect of magnesium sulphate on the colonization of maize roots by a vesicular-arbuscular mycorrhizal fungus was studied in hydroponic culture. Increased concentration of MgSO4 in the nutrient solution caused an increase in the percentage of root length infected. The highest infection levels were found when nutrient solutions contained 5 84-11.68 mmol 1-1 of MgSO4 . Root colonization was stimulated by the increased concentration of magnesium but not calcium or potassium ions in the nutrient solution. No significant difference occurred in the percentage of root length infected when magnesium chloride was replaced by magnesium sulphate. A broad range of magnesium sulphate concentrations did not cause significant differences in plant biomass. The stimulation of root colonization by magnesium cannot be explained by changes in pH or osmotic pressure of the nutrient solution.
Keywords: VA mycorrhiza; hydroponic culture; maize; Glomus; Magnesium